Righting Wrongs: A Handbook of Child Rights for Teachers - Gulati, Nidhi (Voices of Teachers and Teacher Educators, 2021)
The book Righting Wrongs engages with child rights. It focuses on key developments in law, policy and practices linked to child rights. The book attempts to highlight socio-cultural practices, beliefs and conventions that lead to denial or violation of rights. Few books exist that engage with these concerns, particularly those that serve as resources for children and teachers. This text attempts to fill this gap, and is designed as a handbook of information, resources and activities for teachers to use with children in formal and informal settings